Uma contribuição aos procedimentos de otimização aplicados a sistemas mecânicos - Faria, Mário Luiz de Mendonça (1991)
A combination of a group of numerical and computa- tional techniques of nonlinear programming is presented, focusing the engineering design optimization. The Augmented Lagrange Multiplier Method is used to deal with the constrained problem and the algorithm due to Davidon, Fletcher and Powell for the unconstrained optimization. Line searches are made using the Golden Section and the Polinomial Aproximation techniques. Different applications examples of the computational program which results of the combined procedures are presented to emphasize the methodology efficacy on the minimization of mathematical functions, as well. as on the optimization of typical problems related to mechanical systems design.